2017
DOI: 10.3127/ajis.v21i0.1570
|View full text |Cite
|
Sign up to set email alerts
|

Trauma, Shared Recognition and Indigenous Resistance on Social media

Abstract: This paper investigates the ways in which Indigenous Australians respond individually, and collectively, to racial vilification by means of social media sites. Introducing the concept of "shared recognition" this paper describes the collective sense of anger and frustration experienced by Indigenous people when traumatic events in the public domain act as reminders of ongoing colonialism. Three examples are explored to demonstrate collective trauma as a result of racist and discriminatory acts that are made pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 27 publications
(18 reference statements)
0
35
0
Order By: Relevance
“…Common alternate names used included, but were not limited to, cocreation, self-determination, 2-way communication, and self-design [11,20,25,26]. Most studies focused on the positive elements of improving Aboriginal health; this is in contrast to much of the previous literature, which framed their research around “disease” and the problems associated with the disease rather than “health.” Other work has investigated social media and its role in racial vilification [9]. The examples analyzed in this study show that social media has significant negative and detrimental impacts on Aboriginal people as they are reminded of colonization.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Common alternate names used included, but were not limited to, cocreation, self-determination, 2-way communication, and self-design [11,20,25,26]. Most studies focused on the positive elements of improving Aboriginal health; this is in contrast to much of the previous literature, which framed their research around “disease” and the problems associated with the disease rather than “health.” Other work has investigated social media and its role in racial vilification [9]. The examples analyzed in this study show that social media has significant negative and detrimental impacts on Aboriginal people as they are reminded of colonization.…”
Section: Discussionmentioning
confidence: 88%
“…The examples analyzed in this study show that social media has significant negative and detrimental impacts on Aboriginal people as they are reminded of colonization. However, the authors acknowledge that their findings highlight the potential vehicle of social media to have conversations that promote change [9]. In addition, a recent study has found that Australian Aboriginal people interact about their health using social media [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The arts (e.g., music, storytelling, photography) have been particularly effective at relaying IPs' fights against pollution to global audiences and inspiring social and policy action towards pollution issues affecting IP (Branagan 2005; Gillespie 2013; Horton 2017). Increasing presence of IPs on social media (Carlson et al 2017; Nunn 2018) is also contributing to give visibility to conflicts around pollution (Örestig and Lindgren 2017). For example, contestation of resource extraction can be traced through digital media in Inuit communities (Scobie and Rodgers 2013).…”
Section: Resultsmentioning
confidence: 99%
“…A 2014 survey with a national sample of 400 Indigenous participants estimated that 60% of Indigenous people used Facebook, compared to 42% of the Australian population at that time (McNair Ingenuity Research, 2014). Other research has found that social media is used in a range of ways by Aboriginal and Torres Strait Islander people, including developing and expressing Indigenous identity (Carlson, 2013; Kral, 2014; Rice et al , 2016,), seeking and offering help for issues relating to suicide and self-harm (Carlson et al , 2015), citizen journalism (Sweet et al , 2013), online activism and countering racism and negative stereotypes (Petray, 2013; Sweet et al , 2015; Korff, 2016; Carlson et al , 2017).…”
Section: Introductionmentioning
confidence: 99%